Inovasi Pemanfaatan Botol Bekas sebagai Media Edukasi Literasi Finansial bagi Siswa SDN 13 Ulakan Tapakis - Refdinal Refdinal; Nadia Erwanda; Nisaul Latifah Atta; Fitri Nur Nazmi; Winda Denita; Gema Pratama Mahadi Putera (CV. ITTC INDONESIA, 2026)
The low saving culture in Indonesia, where the saving ratio to GDP is only 34.8 percent compared to neighboring countries, is the background for the urgency of financial education from an early age. Unlike conventional socialization which is only based on material presentation, this research offers novelty through an integrative approach to utilizing used bottle waste as a creative piggy bank medium. This study aims to shape saving behavior and financial management understanding in students of SDN 13 Ulakan Tapakis, Padang Pariaman Regency. The method used is descriptive qualitative with data collection techniques through participatory observation, in-depth interviews, and documentation. Research findings show that the use of used bottle media significantly increases visual engagement and students' interest in setting aside pocket money. In addition, this activity was able to shift the consumptive behavior of students who were previously exposed to the negative impacts of social media into frugal behavior with the ability to distinguish between needs and wants. The integration of this creative media proved effective in instilling financial independence and preventing the risk of dependence on loans in the future.